Caracterização de surimi obtido a partir da carne mecanicamente separada de tilápia do Nilo e elaboração de fishburger - Santos Fogaca, Fabiola Helena dos; Otani, Fabrizia Sayuri; De Gaspari Portella, Carolina [UNESP]; Alves dos Santos-Filho, Luiz Gonzaga; Sant'Ana, Lea Silvia [UNESP] (Univ Estadual Londrina, 2015)
The aim of this study was to obtain products (surimi and fishburger) from mechanically separated meat (MSM) of Nile tilapia (Oreochromis niloticus), and evaluate its aspects chemical, microbiological, nutritional and sensory attributes. For fishburger preparation the MSM was submitted to successive washes cycles, to obtaining a protein concentrate defined as surimi. The composition of MSM and surimi was determined by analysis of moisture, protein, lipid and amino acid profile. Microbiological analysis were performed for Staphylococcus sp., coliforms at 45 degrees C and Salmonella sp. Sensory analysis of fishburger was performed by the global acceptance testing, for evaluation of parameters such as general appearance, odor, flavor and texture. The surimi showed lower protein (14.81%) and lipid (7.15%) content and higher moisture (75.44%) compared to the MSM (P < 0.05). The amiprofile of MSM and surimi was similar, with high nutritional value caused by its essential amino acids presence. Microbiological analysis showed that the product was according with the sanitary standard required. Sensorial analysis determined notes near to 7.0 for appearance, flavor, odor, texture and overall acceptability. Based on these results, it is concluded that the surimi can be used in the preparation of fishburger by presenting desirable attributes for sensory, nutritional and microbiological parameters, and encourage the use of co-products generated in the tilapia filleting industry.

Este estudo teve como objetivos obter produtos (surimi e fishburger) a partir da carne mecanicamente separada (CMS) de tilápia do Nilo (Oreochromis niloticus) e avaliar seus aspectos químicos, microbiológicos, nutricionais e sensoriais. Para elaboração do fishburger, a CMS foi submetida a lavagens sucessivas, obtendo-se um concentrado protéico definido como surimi. A caracterização química da CMS e do surimi foi determinada pelas análises da composição química (umidade, proteína e lipídeos) e do perfil de aminoácidos. As análises microbiológicas foram realizadas para Estafilococos, coliformes a 45 °C e Salmonella sp. A análise sensorial do fishburger foi realizada por meio da aplicação do teste de aceitação global, avaliando-se parâmetros como aparência, sabor, odor e textura. O surimi apresentou menores teores proteico (14,81%) e lipídico (7,15%) e maior umidade (75,44%) em comparação à CMS (P<0,05). Os perfis de aminoácidos da CMS e do surimi foram semelhantes, apresentando alto valor nutricional pela sua composição de aminoácidos essenciais. A análise microbiológica demonstrou que o produto estava dentro do padrão sanitário exigido pela legislação. A análise sensorial obteve notas próximas de 7,0 para aparência, sabor, odor, textura e aceitação geral. Com base nos resultados obtidos, conclui-se que o surimi pode ser utilizado na elaboração do fishburger por apresentar atributos sensoriais, nutricionais e microbiológicos desejáveis e por estimular o aproveitamento dos coprodutos gerados na filetagem da tilápia
Characterization of surimi from mechanically deboned tilapia meat and fishburger preparation
Keywords: Amino acids; Global test; Quality attributes; Minced; Aminoácidos; Aceitação global; Atributos de qualidade; CMS